2020
DOI: 10.5430/ijfr.v11n2p196
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Indonesia Stock Exchange: A Multi-Index Approach

Abstract: This study examines the influence of world and regional capital market conditions on the Indonesian capital market (Indonesia Stock Exchange) condition. The DJIA (Dow Jones Industrial Average) index was used as a representative of the international capital market while the Hang Seng index and the Nikkei 225 index were used as a representative of regional capital market conditions. These two indices were chosen because the Japanese capital market was one of the most advanced capital markets in the world and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Several studies in Indonesia have also reported factors that affect the stock index. Susilo et al (2020) reported a significant positive impact of the Dow Jones Industrial Average (DJIA) and Hang Seng Index on IHSG, while the Nikkei 225 index did not. Other findings suggest that the BI rate also affects the stock index, but its influence may be complex and influenced by other factors (Yusuf et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in Indonesia have also reported factors that affect the stock index. Susilo et al (2020) reported a significant positive impact of the Dow Jones Industrial Average (DJIA) and Hang Seng Index on IHSG, while the Nikkei 225 index did not. Other findings suggest that the BI rate also affects the stock index, but its influence may be complex and influenced by other factors (Yusuf et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Financial statement analysis is an essential aspect in assessing the company's financial condition, which is carried out based on the company's financial ratio analysis conducted in a particular year. Ratio analysis can be grouped into 5 (five) categories: liquidity ratios, activity ratios, solvency ratios, market ratios, and profitability ratios (Susilo et al, 2020;Hamal & Gautman, 2021). The author intends to use an internal fundamental analysis approach in this study.…”
Section: Introductionmentioning
confidence: 99%